1996
DOI: 10.1021/bp960025v
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mass Transfer Kinetics of BSA on a TSK-GEL DEAE-5PW Anion Exchanger in a Wide Concentration Range

Abstract: The adsorption isotherms of bovine serum albumin (BSA) on TOSOHAAS TSK-GEL DEAE-5PW were determined in a pH ) 7.5 buffer for a 1.0 mL/min flow rate and at pH ) 6.0 for 1.0, 2.0, and 3.0 mL/min flow rates. The isotherm data were derived from the breakthrough curves obtained by step series frontal analysis (FA) method. The sample concentrations ranged from ca. 0.2 to 3 mg/mL. From the Scatchard plots, it was found that the bi-Langmuir isotherm model fits the adsorption isotherm data better than the single Langmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
32
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 17 publications
9
32
0
Order By: Relevance
“…dependence of both km,L of BSA 17,18 and km of Tröger's base 19 reported previously [8][9][10][11] and derived new information concerning the mass transfer characteristics of the four transport processes described above. In the case of anion exchange separation of BSA, 17,18 it was shown that surface diffusion played a predominant contribution in the kinetic properties of mass transfer and that the linear concentration dependence of km,L probably resulted from that of the surface diffusion coefficient (Ds).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…dependence of both km,L of BSA 17,18 and km of Tröger's base 19 reported previously [8][9][10][11] and derived new information concerning the mass transfer characteristics of the four transport processes described above. In the case of anion exchange separation of BSA, 17,18 it was shown that surface diffusion played a predominant contribution in the kinetic properties of mass transfer and that the linear concentration dependence of km,L probably resulted from that of the surface diffusion coefficient (Ds).…”
supporting
confidence: 61%
“…The extent of the positive concentration dependence of km,L was larger for L-PA than for D-PA. It is expected that a more detailed analysis of the overall mass transfer rate parameter, km,L, could provide new, useful information and allow for a better understanding of the kinetic properties of imprinted stationary phases.A similar positive concentration dependence was also demonstrated for km,L in anion exchange chromatography of bovine serum albumin (BSA), 8,9 and for the mass transfer rate coefficient (km) in the enantiomeric separation of Tröger's base on microcrystalline cellulose triacetate. 10,11 In other previous publications, a concentration dependence was also confirmed for intraparticle diffusivity, 12 for tracer diffusivity, 13 for axial dispersion, 14 for effective diffusivity, 15 and for mutual diffusion coefficients.…”
supporting
confidence: 56%
“…However, the discrepancy between it and the theoretical curve calculated by the E-D model turns out to be significant. This result is as expected, because the E-D model will not be suited for affinity separations where the kinetics are slow [28][29][30][31]. The Thomas model concerns the effect of sorption kinetics and has been used to describe the breakthrough curves obtained in MAC [12,18].…”
Section: Application Of the Mp Model In Macsupporting
confidence: 63%
“…It is assumed that k m,L is constant during each concentration step in the FA measurement and that k m,L corresponds to the average concentration of this step. By using this method, Guan-Sajonz et al [27] and Sajonz et al [28] measured the rate of the mass transfer kinetics of bovine serum albumin in ion exchange chromatography, using anion exchange resins. Seidel-Morgenstern et al [29] and Rearden et al [30] studied the mass transfer kinetics of Tröger's base in the phase system of cellulose triacetate and ethanol.…”
Section: Fluorescence Relaxationmentioning
confidence: 99%